Features of the educational process of students in distance learning system Moodle - Yu. M. Penkin; N. M. Iatsenko (Zaporozhye State Medical University, 2014)
The paper analyzes the characteristics of distance learning in Moodle. On the example of a distance course «Information Technology in Pharmacy», developed at the National University of Pharmacy, the work with all the information and educational resources available in the system Moodle is shown, as well as the advantages and disadvantages of distance learning.